2004
DOI: 10.1080/13590840410001735036
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Lactulose Breath Hydrogen Measurements with Gut Fermentation Profiles in Patients with Fungal‐type Dysbiosis

Abstract: Purpose: Fungal-type dysbiosis (FTD) is still an unproven diagnosis. Patients are polysymptomatic, but most have symptoms of irritable bowel. Treatment, using a diet low in fermentable, yeasty and mould-containing foods with or without antifungal drugs, is often rewarding. Patients with FTD show elevated blood ethanol levels after fasting glucose challenge. Because of this most authors suggest a fungal cause. Hydrogen generation is a bacterial fermentation product and would only be expected if a bacterial caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…A number of such patients have an excess of urinary b -alanine excretion [5], which again is not present in patients with food intolerance. Other studies have shown that patients with FTD show reduced levels of B vitamins, zinc and magnesium [6], increased gut permeability [4], lowered urinary histidine excretion [7] and a high incidence of elevated breath hydrogen levels [8]. In these studies, there are no signi cant differences between an FTD group and one with food intolerance, although both have a high incidence of abnormality as compared with healthy controls.…”
Section: Introductionmentioning
confidence: 95%
“…A number of such patients have an excess of urinary b -alanine excretion [5], which again is not present in patients with food intolerance. Other studies have shown that patients with FTD show reduced levels of B vitamins, zinc and magnesium [6], increased gut permeability [4], lowered urinary histidine excretion [7] and a high incidence of elevated breath hydrogen levels [8]. In these studies, there are no signi cant differences between an FTD group and one with food intolerance, although both have a high incidence of abnormality as compared with healthy controls.…”
Section: Introductionmentioning
confidence: 95%
“…Some tests explore the possibility that intestinal yeasts metabolize an oral glucose load by measuring blood ethanol 1 h after ingestion of a test solution [9,45,46]. These tests have been further developed to include analyses of other alcohols that bacteria, rather than yeast, can produce [6,10]. The test attempts, and has the potential, to identify patients where yeast overgrowth is of sufficient magnitude to produce measurable metabolites in circulation and distinguishes this from bacterial overgrowth, or bacterial dysbiosis [6][7][8]11].…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…These tests have been further developed to include analyses of other alcohols that bacteria, rather than yeast, can produce [6,10]. The test attempts, and has the potential, to identify patients where yeast overgrowth is of sufficient magnitude to produce measurable metabolites in circulation and distinguishes this from bacterial overgrowth, or bacterial dysbiosis [6][7][8]11]. Unfortunately, the glucose challenge test is not specific and cannot show that abnormal findings are due to Candida albicans or, for that matter, any other yeast.…”
Section: Diagnostic Testsmentioning
confidence: 99%
See 2 more Smart Citations